Chapter Solidarietà: un principio generale del diritto internazionale? - PISILLO MAZZESCHI, RICCARDO (Firenze University Press, 2025)
The main question is whether solidarity constitutes a general principle of international law. Scholars are divided on the issue; and this depends on two factors: a) differences in the meaning given to the concept of solidarity; b) differing theories on the nature of general principles of international law. On the first point, the theories that identify solidarity with cooperation are not convincing, and one must instead adhere to a more restrictive concept. On the second point, three different categories of general principles must be admitted. Investigating some regulatory areas potentially relevant to solidarity, we conclude that the principle has a binding nature in some areas, is programmatic in others, and finally does not operate in other fields.